Paediatric Facial Malformation - A Case Report: Life Sciences-Paediatrics - S, Arvinth; K, Vindhiya; Kumar Reddy, Gaddam Aneesh (International Journal of Life Science and Pharma Research, 2022)
Arteriovenous malformations (AVMs) are rare congenital vascular malformations. They account for 1.5% of all vascular anomalies. Oral and maxillofacial regions are the common sites and account for 50% of the cases. We report a seven-year-old female child with progressive left cheek swelling for the past two years. There was no pain, dysphagia or difficulty in chewing food. But the swelling caused significant cosmetic concern due to facial disfigurement. There was a history of cystic hygroma, operated at a young age. There is no significant family history of vascular anomalies. Child was investigated and diagnosed to have slow flow vascular malformation. Treatment is a multidisciplinary approach. Minimally invasive procedures can conservatively manage it by injecting drugs. Other options are laser therapy, open surgery and a combination of the above treatments. Our case improved after multiple cycles of foam sclerotherapy. Many cases might not improve with one or two injections, but it requires multiple doses. Arteriovenous malformation is not only a physical problem but also involves psychological concern for the child. Though it may be a benign condition, it might cause facial disfigurement, as in our case. A high index of suspicion is required as it is incidentally diagnosed during dental procedures. Multimodality therapy is necessary for the management and is beneficial in all age groups. The present case is published for its rarity.